2015
DOI: 10.1039/c5cp00231a
|View full text |Cite
|
Sign up to set email alerts
|

Influence of chlorine coordination number on the catalytic mechanism of ruthenium chloride catalysts in the acetylene hydrochlorination reaction: a DFT study

Abstract: The catalytic mechanism of Ru-based catalysts in the acetylene hydrochlorination reaction has been investigated via the density functional theory (DFT) method. To study the effect of the chlorine coordination number on the catalytic mechanism, Ru3Cl9, Ru3Cl7, Ru5Cl7, Ru3Cl3 and Ru3 clusters were chosen as the catalytic models. Our results show that the energy barrier for acetylene hydrochlorination on Ru3Cl9 was as high as 1.51 eV at 458 K. When the chlorine coordination number decreased, the energy barriers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…The results of this study show that the activation of HCl is the key to improve the catalyst life in this reaction, which is in agreement with previous studies [7,25,[66][67][68]. However, it remains challenging to enhance the adsorption or activation of HCl because the H-Cl bond is sturdy (428 kJ/mol of bond energy) [69].…”
Section: Pattern Of Catalytic Mechanism In This Systemsupporting
confidence: 90%
“…The results of this study show that the activation of HCl is the key to improve the catalyst life in this reaction, which is in agreement with previous studies [7,25,[66][67][68]. However, it remains challenging to enhance the adsorption or activation of HCl because the H-Cl bond is sturdy (428 kJ/mol of bond energy) [69].…”
Section: Pattern Of Catalytic Mechanism In This Systemsupporting
confidence: 90%
“…It can be concluded that RuCl 3 and BaCl 2 are non-polar molecules (zero dipole moment) with regular plane triangular and linear structure, respectively, while AuCl 3 demonstrates an isosceles triangular structure with a dipole moment of 0.0671 Debye. Other references also confirmed these specific structures [12][13][14][15][16].…”
Section: Selection and Structure Of Metal Chloridessupporting
confidence: 55%
“…Among a wide variety of available nonmercuric catalysts, Hutchings and other researchers have found that many metal catalysts, such as Au, [8][9][10] Pd, [11,12] Ru, [13][14][15][16] Cu, [17] and so on, all showed high catalytic activities and could be used as substitutes for HgCl 2 in acetylene hydrochlorination. To meet economic benefits, Cu-based catalysts are definitely becoming a research hotspot, [18] and researchers have been pursuing and aiming to improve the catalytic activity and stability.…”
mentioning
confidence: 99%